Optimizing Concussion Care Seeking: A Longitudinal Analysis of Recovery. Issue 1 (January 2023) - Schmidt, Julianne D.; Broglio, Steven P.; Knight, Kristen; Leeds, Daniel; Lynall, Robert C.; D'Lauro, Christopher; Register-Mihalik, Johna; Kroshus, Emily; McCrea, Michael; McAllister, Tom W.; Kerr, Zachary Y.; ,; et al.
Background: Approximately half of concussions go undisclosed and therefore undiagnosed. Among diagnosed concussions, 51% to 64% receive delayed medical care. Understanding the influence of undiagnosed concussions and delayed medical care would inform medical and education practices. Purpose: To compare postconcussion longitudinal clinical outcomes among (1) individuals with no concussion history, all previous concussions diagnosed, and ≥1 previous concussion undiagnosed, as well as (2) those who have delayed versus immediate symptom onset, symptom reporting, and removal from activity after concussion. Study Design: Cohort study; Level of evidence, 2. Methods: Participants included 2758 military academy cadets and intercollegiate athletes diagnosed with concussion in the CARE Consortium. We determined (1) each participant's previous concussion diagnosis status self-reported at baseline (no history, all diagnosed, ≥1 undiagnosed) and (2) whether the participant had delayed or immediate symptom onset, symptom reporting, and removal from activity. We compared symptom severities, cognition, balance, and recovery duration at baseline, 24 to 48 hours, date of asymptomatic status, and date of unrestricted return to activity using tests of parallel profiles. Results: The ≥1 undiagnosed concussion group had higher baseline symptom burdens ( P < .001) than the other 2 groups and poorer baseline verbal memory performance ( P = .001) than the all diagnosed group; however, they became asymptomatic and returned to activity sooner than those with no history. Cadets/athletes who delayed symptom reporting had higher symptom burdens 24 to 48 hours after injury (mean ± SE; delayed, 28.8 ± 0.8; immediate, 20.6 ± 0.7), took a median difference of 2 days longer to become asymptomatic, and took 3 days longer to return to activity than those who had immediate symptom reporting. For every 30 minutes of continued participation after injury, days to asymptomatic status increased 8.1% (95% CI, 0.3%-16.4%). Conclusion: Clinicians should expect that cadets/athletes who delay reporting concussion symptoms will have acutely higher symptom burdens and take 2 days longer to become asymptomatic. Educational messaging should emphasize the clinical benefits of seeking immediate care for concussion-like symptoms.